Amino Acid Signatures to Evaluate the Beneficial Effects of Weight Loss - Nina Geidenstam; Martin Magnusson; Anders P. H. Danielsson; Robert E. Gerszten; Thomas J. Wang; Lovisa E. Reinius; Hindrik Mulder; Olle Melander; Martin Ridderstråle (International Journal of Endocrinology)
Aims. We investigated the relationship between circulating amino acid levels and obesity; to what extent weight loss followed by weight maintenance can correct amino acid abnormalities; and whether amino acids are related to weight loss. Methods. Amino acids associated with waist circumference (WC) and BMI were studied in 804 participants from the Malmö Diet and Cancer Cardiovascular Cohort (MDC-CC). Changes in amino acid levels were analyzed after weight loss and weight maintenance in 12 obese subjects and evaluated in a replication cohort (n=83). Results. Out of the eight identified BMI-associated amino acids from the MDC-CC, alanine, isoleucine, tyrosine, phenylalanine, and glutamate decreased after weight loss, while asparagine increased after weight maintenance. These changes were validated in the replication cohort. Scores that were constructed based on obesity-associated amino acids and known risk factors decreased in the ≥10% weight loss group with an associated change in BMI (R2=0.16–0.22, p<0.002), whereas the scores increased in the <10% weight loss group (p<0.0004). Conclusions. Weight loss followed by weight maintenance leads to differential changes in amino acid levels associated with obesity. Treatment modifiable scores based on epidemiological and interventional data may be used to evaluate the potential metabolic benefit of weight loss.